INDONESIAN LOCAL FERMENTATION FUNCTIONAL FOOD DEVELOPMENT STRATEGY IN THE ERA OF PANDEMIC COVID 19 - Muchamad Bachtiar; Heny Herawati (Journal of Islamic, Social, Economics and Development, 2022)
Local fermented foods in Indonesia are highly diversed. It is commercially prospective to develope into higher value added products. Indonesian traditional custom food regional-based has special characters to enter specific market segmentation, especially for local fermented food. Several processed and fermented products are tempeh, kefir, tauco, tape, nata de coco, bekasam, etc. The Covid 19 pandemic era has provided changes in market segmentation to start consuming functional foods that provide health benefits. Several bioactive components and health benefits can be found in those local fermented foods. This situation also provided a changes in the online marketing system-based that beneficial for those to access and shortens the supply chain, however, constrain of fermented product is their different â€œbest timeâ€ to consume due to biological microbe mechanism. This issue need to solve by implementing excellent strategy, a combination of fulfillment on demand side timely and excellent quality product that affect by biological microbe mechanism. The strategy in ensuring product quality by controlling a several factors during processing and distribution so that the functional local fermented food products are still fit to consume and provide health benefits. In this paper, we examine important strategies for the development of local fermented functional food in Indonesia in the Covid 19 Pandemic Era.